Espoused Values and Organizational Change Themes - Kabanoff, Boris; Waldersee, Robert; Cohen, Marcus (Academy of Management Journal, 1995)
Using computer-aided content analysis, we assessed the strength of nine values?authority, performance, reward, normative, commitment, participation, leadership, teamwork, and affiliation?in 88 large Australian organizations. Cluster analysis was used to categorize each organization as having one of four value structures: elite, leadership, meritocratic, or collegial. Organizations classified as having different value structures differed in a theoretically consistent way in how their members described organizational change. We discuss the implications of these findings for the values theory and the use of content analysis for the study of organizational values.